Hallucinations, an existential crisis?. Issue 2 (31st August 2011) - Nikolov(a), Jennifer Kanary
Having hallucinations is often seen as one of the key symptoms of mental health problems, in particular to those of schizophrenia. In the DSM-IV, hallucinations are defined as follows: 'A sensory perception that has the compelling sense of reality of a true perception, but that occurs without external stimulation of the relevant sensory organ'. But what is a true perception? And how do we know whether there really is no external stimulation? With people so unanimously convinced that what they are going through is not illness, but an awakening to the nature of reality. And with more and more documentaries being created about the illusionary nature of our reality, we might want to take a closer look at the descriptions of people who suffer from what is known as a reality disorder. We might think about how this might inform us about the nature of reality in a way that would diminish the existing stigma that surrounds psychosis and schizophrenia. We might even wonder whether the concept of hallucination has the right to exist.